2014 4th Joint Workshop on Hands-Free Speech Communication and Microphone Arrays (HSCMA) 2014
DOI: 10.1109/hscma.2014.6843239
|View full text |Cite
|
Sign up to set email alerts
|

Ad-hoc microphone array calibration from partial distance measurements

Abstract: We address the problem of ad hoc microphone array calibration where some of the distances between the microphones can not be measured. The conventional techniques require information about all the distances for accurate reconstruction of the array geometry. To alleviate this condition, we propose to exploit the properties of Euclidean distance matrices within the framework of low-rank matrix completion to recover the missing entries. We provide rigorous analysis to bound the calibration error using noisy measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…For microphone array calibration, some advanced mathematical methods use joint source and microphone localization methods [62] and incorporate matrix completion constrained by Euclidean space properties [63,64]. Such methods require partial knowledge of pairwise microphone distances [65].…”
Section: Microphone Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…For microphone array calibration, some advanced mathematical methods use joint source and microphone localization methods [62] and incorporate matrix completion constrained by Euclidean space properties [63,64]. Such methods require partial knowledge of pairwise microphone distances [65].…”
Section: Microphone Calibrationmentioning
confidence: 99%
“…For microphone array calibration, some advanced mathematical methods use joint source and microphone localization methods [62] and incorporate matrix completion constrained by Euclidean space properties [63,64]. Such methods require partial knowledge of pairwise microphone distances [65]. It has been shown that using sound emissions for self-calibration can result in a calibration method more robust to sampling frequency mismatch [66]; however, the method is only applicable to devices that have both recording and sound emitting capabilities.…”
Section: Microphone Calibrationmentioning
confidence: 99%
“…Unless Ξ π consists of correct order of images, theM π does not correspond to a Euclidean distance matrix, so we propose to projectM π on to the cone of Euclidean distance matrices, EDM N . To this end, we apply a projection, P : S N h −→ EDM N and measure the distance between the estimated matrix and the EDM cone [26,27].…”
Section: ) Synchronizationmentioning
confidence: 99%